Advances in Knowledge and Management of Immune-Related Adverse Events in Cancer Immunotherapy - Olsen, T. Anders; Zhuang, Tony Zibo; Caulfield, Sarah; Martini, Dylan J.; Brown, Jacqueline T.; Carthon, Bradley C.; Kucuk, Omer; Harris, Wayne; Bilen, Mehmet Asim; Nazha, Bassel (Frontiers in Endocrinology, 2022)
Immune-oncologic (IO) therapy has revolutionized the treatment and management of oncologic disease. Immunotherapy functions by enhancing the host immune-systems ability to endogenously clear malignant cells, however, this activation can also lead to immune-mediated damage to healthy native tissues. These side effects are known as immune-related adverse events or irAEs and can even present with phenotypes similar to autoimmune diseases. IrAEs are the major consequence of checkpoint inhibitors and can have a significant impact on a patient’s cancer treatment and long-term quality of life. The management of these irAEs follows a similar approach to autoimmune diseases. More specifically, the management is akin to that of autoimmune disease exacerbations. While there is an array of immune-suppressing agents that can be used, steroids, immunomodulators and IO discontinuation are cornerstones of irAE management. The exact approach and dosing are based on the severity and subtype of irAE presented. Within recent years, there has been a push to better prevent and manage irAEs when they arise. There has been an additional effort to increase the number of steroid-sparing agents available for irAE treatment given the consequences of long-term steroid therapy as well as patient contraindications to steroids. The goals of this review are to summarize irAE management, highlight significant advances made in recent years and emphasize the future directions that will optimize the use of IO therapy in oncology.